A escola da Vila da Paz: um ensaio etnográfico - OLIVEIRA, Mara Rita Duarte de (Universidade Federal do Pará, 2021)
At the work “School rural da Vila da Paz”: the research about culture, political, economic and social that bucolic community, we Will discuss the program’s execution “School Ativa” at the rural schools from Rondon do Pará, where we’ll analyze the E.M.E.F Vasco da Gama school (located at Vila da Paz society) as the main point of this text. Along all of this study we’ll have questions about how this program improved the students’ knowledge’s and show the teachers a better way of teaching, at the same time we are discussing the population to develop this program, emphasizing the school and community relationship importance. We Will show, at first, the government programs from 1930 until 1990 based on the rustic education is inserted. For this it’s also necessary do na incursion into the educational projects of the social movements connected with the conflicts at the yield